ON TAXONOMIC INVARIANTS OF MACROPHYTE ALGAE AND THEIR VIOLATION UNDER EXPOSURE TO ANTHROPOGENIC FACTORS - B. I. Semkin; L. I. Varchenko; M. V. Gorshkov (Известия ТИНРО, 2019)
New mathematical methods for determining of multicomponent invariants are developed by detection of their constancy using the measures of percentage similarity. Typification of the descriptive sets is proposed. An important type for verification of invariants is considered — generally normalized descriptive sets, with exception of 0 and 1 components. In this type of descriptive sets, the invariants and relative spectra match, the arithmetic mean of multicomponent invariants and the mediant also match. Taxonomic invariants for the macrophyte floras in the Avachinskaya Guba Bay are determined for 1970 and 1991, and their rapid changes under anthropogenic impacts are demonstrated.